Preclinical and clinical development of afatinib: a focus on breast cancer and squamous cell carcinoma of the head and neck. (January 2014) - Harbeck, Nadia; Solca, Flavio; Gauler, Thomas C
ABSTRACT: Aberrant signaling of the ErbB family of receptors plays an integral role in the tumorigenesis of many cancer types, including head and neck squamous cell carcinoma (HNSCC) and breast cancer (BC). Significant research efforts have focused on developing new treatments that target ErbB family members, with the last decade seeing the approval of small-molecule tyrosine kinase inhibitors and monoclonal antibodies that inhibit ErbB signaling. However, treatment resistance is an ever-growing problem and, therefore, new therapies are being investigated to overcome this hurdle. Afatinib is an irreversible ErbB family blocker that has demonstrated potent anti-tumor activity in preclinical models and has displayed clinical efficacy in patients with non-small-cell lung cancer, and activity in HNSCC and BC. Here, the preclinical and clinical development of afatinib in the treatment of non-small-cell lung cancer, HNSCC and BC is described in the context of currently approved agents.